The Evidence and Clinical Rationale for the Use of JAK Inhibitors in the Management of AD (Canadian Allergy & Immunology Today, 2022)
Atopic dermatitis (AD) is one of the most common chronic inflammatory skin diseases affecting 1 in 5 children and 1 in 10–20 adults. AD is characterized by clinical symptoms and signs of erythema, edema, excoriation, lichenification, xerosis, and in pediatric populations, oozing and weeping is more prevalent. Intense itch associated with AD can negatively impact sleep and quality of life. The consequences of sleep disturbance and fatigue may be underdiagnosed in this population. Atopic dermatitis has been associated with medical comorbidities that fall within type 2 inflammatory conditions (e.g., such as asthma, allergic rhinoconjunctivitis, and food allergies) as well as non-type-2 inflammatory conditions such as cardiometabolic disease, infections (both cutaneous and non-cutaneous), anxiety/depression, and autoimmune conditions such impetigo and alopecia aerata. AD has the strongest impairment of life expectancy outside of malignancy when it comes to dermatologic disease. While topical therapies such as topical corticosteroids (TCS), topical calcineurin inhibitors (TCI), and phosphodiesterase 4 (PDE4) inhibitors are effective treatments for most patients with mild-to- moderate AD, more than 90% of those suffering from moderate-to-severe AD report significant unmet need along with the use of multiple therapeutic options, including off-label systemic medications which do not offer symptom control.  Patients with refractory disease commonly receive acute courses oral corticosteroids, if not chronic treatment with systemic therapies, either off-label immunosuppressive agents e.g., methotrexate) or the immunomodulator dupilumab (a monoclonal antibody) targeting components of the inflammatory signature characterizing moderate-to-severe AD. In this paper we review and summarize the role and clinical application of an emerging class of systemic targeted therapy, namely the oral Janus kinase inhibitors (JAKi) in  the treatment and management of moderate-to-severe AD.